Role of liver atrophy, hepatic resection and hepatocyte hyperplasia in the development of portal hypertension in biliary disease. - Hadjis, N S (1987)
Portal fibrosis is considered to be pivotal in the pathogenesis of portal hypertension associated with extrahepatic biliary obstruction. The histological features, however, include diffuse hepatocyte hyperplasia as well as portal fibrosis, but not cirrhosis, and it is possible that the contribution of hepatocyte hyperplasia in the initiation of portal hypertension is equally important. If so, we hypothesised that patients with biliary obstruction and a coincident condition such as liver atrophy, or hepatic resection, with the potential of accelerating the hepatocyte proliferation caused by biliary obstruction itself, might be expected to develop portal hypertension earlier than patients with biliary obstruction alone. To examine this concept we studied 10 patients with postcholecystectomy bile duct stricture, portal hypertension and liver atrophy, or hepatic resection (group I) and compared them with nine patients with postcholecystectomy stricture and portal hypertension, but no atrophy or resection (group II). Portal hypertension was diagnosed a mean 28 months (range 18-48 months) after cholecystectomy in group I compared with 62 months (range 36-100 months) for patients in group II (p less than 0.005 Mann-Whitney test). Thus hepatocyte hyperplasia may be an important part of the mechanism underlying the development of portal hypertension in chronic biliary disease.